A Note on Some Preliminary Observations on the State of Economics Education in Gujarat - Shah, Ketan K. (Arthshastra Indian Journal of Economics & Research, 2018)
This paper was based on my observations and experiences with regard to the pathetic state of economics education in the state of Gujarat. I surmised that the situation may not be very much different in other parts of the country, barring a couple of states and institutions. The quality of economics teaching and learning has fast deteriorated in public sector institutions. Most of the private sector institutions too are not far ahead in terms of imparting economics education in an appropriate way. After discussing the nature of economics in detail, the paper spelled out the causes for the same and suggested some remedies to ameliorate the situation at the earliest before a royal subject dies a poor man's death.